Performance of Guinea Fowl Numida Meleagris Fed Varying Levels of Poultry Droppings - Adeyemo, A.I.; Oyejola, O. (International Journal of Poultry Science, 2004)
Six hundred guinea fowl pullets, 5 week old, were used for a 30 week feeding trial to test the replacement value of poultry droppings (PD) for blood meal, a conventional protein ingredient, in animal feed. Guinea fowl is a wild bird found in the savanna forests of West Africa. There were four dietary treatments namely, 0, 20, 40 and 60% PD replacement of blood meal. The birds were kept in deep litter houses for 20 weeks. Feed and water were offered ad libitum. At the 20th week, 10 birds were randomly selected from each of the four dietary treatments and starved for one day. They were killed in the slaughter house by cutting the neck through the jugular vein. This was used to determine the carcass parameters. The remaining birds were transferred into the layers house, where the following parameters were determined: body weight gain, feed intake, feed conversion, age at first lay, Percentage hen day production, egg weight, shell thickness and yolk colour. Results show that body weight gain and feed conversion decreased with the level of PD in the diet. There was no significant difference between the birds in carcass parameters in all the treatments except in oviduct length where its values decreased with the level of PD in the diet and significant differences (P